2018
DOI: 10.1038/labinvest.2017.108
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a gene expression signature associated with the metastasis suppressor function of NME1: prognostic value in human melanoma

Abstract: SummaryWhile NME1 is well known for its ability to suppress metastasis of melanoma, the molecular mechanisms underlying this activity are not completely understood. Herein, we utilized a bioinformatics approach to systematically identify genes whose expression is correlated with the metastasis suppressor function of NME1. This was accomplished through a search for genes that were regulated by NME1, but not by NME1 variants lacking metastasis suppressor activity. This approach identified a number of novel genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 74 publications
1
16
0
Order By: Relevance
“…Still, increased levels of NME1 negatively correlated with disease stage while NME1 upregulation was positively correlated with poor overall survival and with higher recurrence [55]. Furthermore, in melanoma patients, a NME1-related gene expression signature was reported and linked with increased overall survival [57], pinpointing for a potential tumor suppressor role, but new pro-oncogenic roles, mainly related with the expansion of stem-like features and tumor growth, were recently reported [58]. Considering CDS1, a DNA damage-related function is well-known [59,60] and a screening of several cancer cell lines highlighted that the expression levels of CDS1 are dependent on p53 activity, being inversely correlated with the presence of a functional p53 [61].…”
Section: Discussionmentioning
confidence: 96%
“…Still, increased levels of NME1 negatively correlated with disease stage while NME1 upregulation was positively correlated with poor overall survival and with higher recurrence [55]. Furthermore, in melanoma patients, a NME1-related gene expression signature was reported and linked with increased overall survival [57], pinpointing for a potential tumor suppressor role, but new pro-oncogenic roles, mainly related with the expansion of stem-like features and tumor growth, were recently reported [58]. Considering CDS1, a DNA damage-related function is well-known [59,60] and a screening of several cancer cell lines highlighted that the expression levels of CDS1 are dependent on p53 activity, being inversely correlated with the presence of a functional p53 [61].…”
Section: Discussionmentioning
confidence: 96%
“…These genes were PTEN , CDC42EP5 , RNLS, GP2 , NETO2 , and AMPD3 . Overexpression of Neuropilin and tolloid-like 2 ( NETO2 ) has been found in many cancer types including proliferating hemangiomas and colorectal carcinoma [24] , [25] , [26] and thus could be considered as a potential biomarker in tumor progression. Recent study have suggested that adenosine monophosphate deaminase 3 ( AMPD3 ) deletion suppresses the proliferation, migration, and invasion of gastrointestinal stromal tumor [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, NME1 directly enhances the expression of aldolase C by binding to its promoter [91]. Moreover, using a bioinformatics approach, aldolase C has been identified as one of the genes establishing the NME1-regulated Metastasis Suppressor Signature (MSS) [92]. It would be of interest to see if other genes that make up the MSS are also phosphorylated by NME on histidine or aspartate.…”
Section: Nme Binding Partnersmentioning
confidence: 99%